Bounds on the Spectral Radius of a Nonnegative Matrix and Its Applications - Danping Huang; Lihua You (Journal of Applied Mathematics)
We obtain the sharp bounds for the spectral radius of a nonnegative matrix and then obtain some known results or new results by applying these bounds to a graph or a digraph and revise and improve two known results.